Zinc oxide nanoclusters and nanoparticles as a drug carrier for cisplatin and nedaplatin anti-cancer drugs, insights from DFT methods and MC simulation. (19th March 2021) - Abd El-Mageed, H.R.
ABSTRACT: In this work, we study the ability of (Zno) n ( n = 2–5 and 12) nanoclusters and ZnO nanoparticles to act as a drug carrier for cisplatin and nedaplatin drugs by DFT methods and MC simulation. Binding energies in both gas and water phases are calculated, the bonds formed between (ZnO)n ( n = 2–5 and 12) and cisplatin and nedaplatin drugs are studied and computed using QMAIM. The binding energy in water is lower than that in gas, which supports that the partially covalent and partially electrostatic bonding nature. Also, binding energies in the state of (ZnO) n -cisplatin complexes are lower than those in the (ZnO) n -nedaplatin complexes in both gas and water phases. Also, the adsorption of cisplatin and nedaplatin drugs on ZnO nanoparticles surface (different sizes and shapes) was studied by Monte Carlo simulation. We find that increasing the ZnO size dose not significantly influences on the adsorption energies of cisplatin and nedaplatin drugs for all studied nanoparticles shapes. All adsorption energies obtained by MC calculations are negative which revealed that the adsorption of the cisplatin and nedaplatin molecules on ZnO surfaces is exothermic, spontaneously and energetically favourable. So, ZnO nanoclusters and nanoparticles can act as a drug carrier for cisplatin and nedaplatin anticancer drugs. Abbreviations: Density Functional Theory; MC simulation : Monte Carlo simulation; QMAIM : quantum mechanics atoms in molecules GRAPHICAL ABSTRACT: